Performance Comparison of Zn-Based and Al–Si Based Coating on Boron Steel in Hot Stamping - Long Chen (MDPI AG, 2021)
The coatings of boron steels play an important role in affecting the quality of hot stamping parts, so it is important to evaluate the hot stamping performance of coatings before designing processes. Taking the U-type hot stamping part of boron steel as research objects, the surface quality, microstructure and temperature variation of samples with GA (galvannealed), GI (galvanized) and Al–Si coatings were observed and analyzed to evaluate the anti-oxidation, forming and quenching performances of different coatings. The results show that all the GA, GI and Al–Si coatings could provide good oxidation protection and also act as the lubricants for avoiding the friction damage of sample substrates and die-surface. But the different compositions of GA, GI and Al–Si coatings will contribute the different colors. Under the same deformation degree, the Al–Si coating can provide the best substrate protection and the GI coating will induce cracks in the substrate because of the liquid metal-induced embrittlement phenomenon. There is no significant difference between the quenching performances of GA, GI and Al–Si coatings, and the thermal conductivity of the GI coating is slightly better than Al–Si and GA coatings.